2009
DOI: 10.1007/s12640-009-9084-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Importance of Astrocytes When Screening for Acute Toxicity in Neuronal Cell Systems

Abstract: Reliable, high throughput, in vitro preliminary screening batteries have the potential to greatly accelerate the rate at which regulatory neurotoxicity data is generated. This study evaluated the importance of astrocytes when predicting acute toxic potential using a neuronal screening battery of pure neuronal (NT2.N) and astrocytic (NT2.A) and integrated neuronal/astrocytic (NT2.N/A) cell systems derived from the human NT2.D1 cell line, using biochemical endpoints (mitochondrial membrane potential (MMP) depola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…It has also been found that NT2A cells are coupled via connexin 43 containing gap junctions [20]. In addition, in our laboratory we have used the NT2N/NT2A co-culture system, to demonstrate that astrocytes confer significantly increased neuronal resilience to chemical toxicity and that neurons and astrocytes display markedly differential sensitivities to a number of CNS toxins [22], [23]. Such findings therefore provide evidence of the distinct functionality of NT2A cells.…”
Section: Introductionmentioning
confidence: 76%
“…It has also been found that NT2A cells are coupled via connexin 43 containing gap junctions [20]. In addition, in our laboratory we have used the NT2N/NT2A co-culture system, to demonstrate that astrocytes confer significantly increased neuronal resilience to chemical toxicity and that neurons and astrocytes display markedly differential sensitivities to a number of CNS toxins [22], [23]. Such findings therefore provide evidence of the distinct functionality of NT2A cells.…”
Section: Introductionmentioning
confidence: 76%
“…Numerous discrete biochemical effects can lead to cytoskeleton changes and the degradation of NFs is widely considered a mandatory component of neurodegeneration following treatment with many neurotoxicants, irrespective of their primary mode of action (Schmuck and Kahl 2009). Indeed, the use of flow cytometry and S-C ELISAs can be complemented by assays focussed on the cellular consequences of reactive species generation, such as GSH, mitochondrial membrane potential and ATP determination (Woehrling et al 2010), thus illuminating the roles of such species in the cell structural responses seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of the NT2.D1 Cell Line to Give NT2.N, NT2.N/A or NT2.A Cultures Production of NT2.N, NT2.N/A or NT2.A cultures from the NT2.D1 cells was performed as previously described (Woehrling et al 2010). Briefly, NT2 cells were differentiated using advanced DMEM medium, supplemented with 2% (v/v) foetal bovine serum (FBS), 2 mM L-glutamine, 1% (v/v) pen/strep (10,000 U penicillin and 10 mg streptomycin/ml concentrate) and 1 9 10 -5 M all-trans retinoic acid (RA) for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations